IDENTIFYING THE ABSORPTION OF BUSINESS ADMINISTRATION GRADUATES IN INDUSTRIES THROUGHOUT EAST KALIMANTAN - Umi Zunaidah; Armini Ningsih; Andi Syarifuddin (CV. RADJA PUBLIKA, 2025)
The relevance of the study field and employment is crucial in the context of the Tracer Study for the Applied Marketing Management program, as it indicates the efficacy of the education received by graduates. Once graduates obtain positions relevant to their studies, it indicates that the curriculum and instructional materials correlate by industry needs, therefore assisting their adjustment into the workforce. The analysis of alumni job status on Tracer study indicates the data is essential for the academic program. In evaluating the effectiveness of graduates in obtaining positions and the relevance of their education. The Tracer study results indicate 71% of alumni have successfully secured employment in diverse companies. Indicating effective job placement and pertinence of the study program's industry. This signifies that the education offered has effectively equipped graduates to confront the problems of the workforce. Furthermore, 12% of alumni pursue further education, 10% successfully establish their own businesses, ensuring succeeding academic entrepreneurship, and 7% work as managers in companies.